THE EFFECT OF WOUND CLEANSING WITH ELECTROLYZED STRONG WATER ACID (ESWA) ON THE HEALING OF DIABETIC FOOT ULCERS (DFU) - Imroatul Farida; Bahtyar Hardyansyah Syihab; Ceria Nurhayati (Bagian Keperawatan Fakultas Kedokteran Universitas Sriwijaya, 2026)
Aim: Diabetic foot ulcers (DFUs) are a chronic complication of diabetes mellitus that carries a risk of infection, amputation, and increased mortality. Selecting the right wound cleansing solution plays a crucial role in supporting the wound healing process, but evidence regarding the effectiveness of Electrolyzed Strong Water Acid (ESWA) in DFU patients is limited. This study aimed to analyze the effect of wound cleansing using ESWA on DFU healing compared to normal saline. Methods: This study used a quasi-experimental, post-test-only control group design and was conducted at Rumah Luka Surabaya from April 29 to May 29, 2019. A total of 100 respondents were selected using simple random sampling and divided into a treatment group receiving ESWA wound cleansing (n=50) and a control group receiving normal saline (n=50). Wound healing was evaluated using the Bates-Jensen Wound Assessment Tool (BWAT) every three days for one month. Data analysis was performed using the Mann-Whitney test. Results: The mean BWAT score in the treatment group was lower than in the control group (20.25 vs. 25.18), with a mean decrease of 16.75 and 11.07, respectively. Both groups were in the wound regeneration category. The Mann-Whitney test showed no significant difference between the two groups (p=0.078). Conclusion: Wound cleansing using ESWA did not have a statistically significant effect on DFU healing compared to normal saline. However, the group receiving ESWA showed a trend toward better clinical improvement, suggesting ESWA has the potential to be used as an antibacterial and relatively economical alternative for wound cleansing in DFU patients.